2022
DOI: 10.1186/s12885-022-09707-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel mitophagy-related gene prognostic signature for glioblastoma multiforme

Abstract: Background Glioblastoma multiforme (GBM) is one of the most malignant tumors in brain with high morbidity and mortality. Mitophagy plays a significant role in carcinogenesis, metastasis, and invasion. In our study, we aim to construct a mitophagy-related risk model to predict prognosis in GBM. Methods RNA-seq data combined with clinical information were downloaded from TCGA. The 4-gene risk model and nomograph was then constructed and validated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Recently, several studies have constructed risk prediction models for different cancers, including pancreatic cancer [25], glioblastoma [26], hepatocellular cancer [27], and lung cancer [28], based on MRGs. The prognostic model constructed based on these 12 MRGs had better predictive accuracy and robustness than the other models, and patients at high risk had worse prognoses in both the training and validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have constructed risk prediction models for different cancers, including pancreatic cancer [25], glioblastoma [26], hepatocellular cancer [27], and lung cancer [28], based on MRGs. The prognostic model constructed based on these 12 MRGs had better predictive accuracy and robustness than the other models, and patients at high risk had worse prognoses in both the training and validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…4 ERGs were eventually selected to calculate the risk score. The formula for performing risk score [ 19 , 20 ] is presented below: where the expr is an expression of the ERGs, and the coef is the corresponding regression coefficient calculated by multi-variant Cox regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The chip platform for the GSE22138 dataset (sample size:63) was the [HG-U133_Plus_2] Affymetrix Human Genome U133 Plus 2.0 Array, as shown in Table 1 . The set of mitophagy-related genes was obtained from Wang et al, (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have shown that mitophagy pathways are intimately associated with the metabolic rearrangement of cancer cells to meet the high bioenergetic needs of tumors ( Vara-Perez et al, 2019 ). Although definitive functional changes and molecular mechanisms of mitophagy have not been completely elucidated, the expression levels of some mitophagy-related genes could serve as biomarkers for the diagnosis, prognosis, or therapy of some cancers ( Wang et al, 2021 ; Wang et al, 2022 ). A recent paper revealed that mitophagy is closely related to the clinical prognosis of patients with UM, and indicated that mitophagy-related biomarkers ( PGAM5, SQSTM1, ATG9A , and GABARAPL1 ) are survival-related genes of UM patients ( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%